Work intensity in sacroiliac joint fusion and lumbar microdiscectomy - Frank C; Kondrashov D; Meyer SC; Dix G; Lorio M; Kovalsky D; Cher D (Dove Medical Press, 2016)
Clay Frank,1 Dimitriy Kondrashov,2 S Craig Meyer,3 Gary Dix,4 Morgan Lorio,5 Don Kovalsky,6 Daniel Cher7 1Integrated Spine Care, Wawautosa, WI, 2St Mary’s Spine Center, San Francisco, CA, 3Columbia Orthopedic Group, Columbia, MO, 4Maryland Brain Spine and Pain, Annapolis, MD, 5Neurospine Solutions, Bristol, TN, 6Orthopaedic Center of Southern Illinois, Mt Vernon, IL, 7SI-BONE, Inc., San Jose, CA, USA Background: The evidence base supporting minimally invasive sacroiliac (SI) joint fusion (SIJF) surgery is increasing. The work relative value units (RVUs) associated with minimally invasive SIJF are seemingly low. To date, only one published study describes the relative work intensity associated with minimally invasive SIJF. No study has compared work intensity vs other commonly performed spine surgery procedures.Methods: Charts of 192 patients at five sites who underwent either minimally invasive SIJF (American Medical Association [AMA] CPT® code 27279) or lumbar microdiscectomy (AMA CPT® code 63030) were reviewed. Abstracted were preoperative times associated with diagnosis and patient care, intraoperative parameters including operating room (OR) in/out times and procedure start/stop times, and postoperative care requirements. Additionally, using a visual analog scale, surgeons estimated the intensity of intraoperative care, including mental, temporal, and physical demands and effort and frustration. Work was defined as operative time multiplied by task intensity.Results: Patients who underwent minimally invasive SIJF were more likely female. Mean procedure times were lower in SIJF by about 27.8 minutes (P<0.0001) and mean total OR times were lower by 27.9 minutes (P<0.0001), but there was substantial overlap across procedures. Mean preservice and post-service total labor times were longer in minimally invasive SIJF (preservice times longer by 63.5 minutes [P<0.0001] and post-service labor times longer by 20.2 minutes [P<0.0001]). The number of postoperative visits was higher in minimally invasive SIJF. Mean total service time (preoperative + OR time + postoperative) was higher in the minimally invasive SIJF group (261.5 vs 211.9 minutes, P<0.0001). Intraoperative intensity levels were higher for mental, physical, effort, and frustration domains (P<0.0001 each). After taking into account intensity, intraoperative workloads showed substantial overlap. Conclusion: Compared to a commonly performed lumbar spine surgical procedure, lumbar microdiscectomy, that currently has a higher work RVU, preoperative, intraoperative, and postoperative workload for minimally invasive SIJF is higher. The work RVU for minimally invasive SIJF should be adjusted upward as the relative amount of work is comparable. Keywords: sacroiliac joint fusion, work intensity, spine surgery, reimbursement